External training loads and soft-tissue injury occurrence during congested versus noncongested periods in football - Barreira, P.; Vaz, J. R.; Ferreira, R.; Araújo, J. P.; Tavares, F. (International Journal of Sports Physiology and Performance, 2024)
Objective To analyze the influence of congested and noncongested fixture periods during 2 seasons in a professional male football team on soft-tissue injury incidence and external load.